Testing the validity of the broaden-and build theory of positive emotions: a network analytic approach - Roth, Leopold Helmut Otto; Bencker, Celine; Lorenz, Johanna; Laireiter, Anton-Rupert (Frontiers in Psychology, 2024)
Introduction The Broaden-and-Build Theory of positive emotions is one of the best known and applied theories in Positive Psychology. It argues that positive emotions initiate an upward movement by opening up the mind and broadening thoughts and thus represents a counter model to the vicious circle-models of clinical psychology. The number of studies directly testing this theory in all components is scarce, ambiguities in the model impede clear inference. Method To draw a conclusive picture on within-model processes, we applied network modeling on the components of the theory across two studies (N1 = 312; N2 = 302). Results In both studies, the positive relationship between positive emotions, resources and life outcomes is well-supported, yet the role of broadening, as an intermediary component within these is questioned. Discussion As the broadening component consistently deviated from the model’s predictions and thus did not contribute to the model as expected in either study, the validity of the Broaden-and-Build Theory in its current conceptualization is challenged, and our results point to the need to reassess the role of broadening.